"Reassessing Syed Muhammad Jaunpuri and the Mahdavi Movement: A Reappraisal of History and Thought : DOI: https://doi.org/10.5281/zenodo.17498703 (Khairulummah, 2023)
This research paper presents an analytical and critical study of the Mahdavi movement within the religious and intellectual history of the Indian subcontinent, focusing on its background, evolution, and the personality and role of its founder, Syed Muhammad Jaunpuri (RA).Drawing upon historical sources such as Muntakhab alTawarikh, TabaqatiAkbari, A’iniAkbari, Akhbar alAkhyar, Nuzhat alKhawatir, and Tadhkira by Abul Kalam Azad, the author demonstrates that Syed Muhammad Jaunpuri (RA) neither claimed prophethood nor divinity, nor did he issue any edict to abandon the essential pillars of Islam such as prayer and fasting.Rather, he was a pious scholar, ascetic, and reformer of Shari‘ah, who launched a movement for amr bil ma‘ruf (enjoining good) and the revival of true Islamic practice amid a period of moral and religious decline. However, his later followers, through excess and misunderstanding, transformed his reformist call into a distinct sectarian identity.The research further establishes that Syed Muhammad Jaunpuri’s contemporariessuch as Shaykh ‘Ali Muttaqi, ‘Abd alHaqq Muhaddith Dehlavi, ‘Abd alQadir Badayuni, and Shaykh Wajih alDin Gujaratipraised his knowledge, piety, asceticism, and spiritual insight, even though they differed with some of his theological interpretations.In conclusion, this paper argues that identifying Syed Muhammad Jaunpuri (RA) as the “Promised Mahdi” is not a reflection of his true teachings, but rather the outcome of later reinterpretations and exaggerations by his followers.Hence, the study serves as a balanced, intellectually moderate, and historically grounded contribution to the understanding of South Asia’s religious reform movementsoffering a valuable scholarly resource for researchers of Sufism and Islamic revivalism.
Keywords: Mahdavi, movement ,Muntakhab alTawarikh,TabaqatiAkbari,fasting